Design of peripheral devices to augment use of unmanned aerial systems in agriculture - Dix, Phillip (Kansas State University, 2018)
This document presents two distinct designs for tools with potential to improve the efficacy of using multirotor aerial systems in agricultural research. I show design methods and results for constructing electrical, mechanical, and software subsystems capable of working in concert to achieve functional results in each design case. The first presented design is a device capable of remotely collecting pest samples directly from a multirotor to improve the speed and efficiency with which researchers and observe and respond to insect infestations. Design concepts, potential improvements, and construction methods are discussed culminating in the presentation of a prototype. The second design presented here is a printed circuit board for integration of a GNSS receiver with Real Time Kinematic correction capability, an IMU for orientation estimation, and a microcontroller with firmware to support, condition, and log data outputs. The purpose of this design is to provide precise logs of position and orientation of an aircraft and attached camera while collecting images of cropland. This reference data allows precise and accurate geolocation of the images and permits them to be stitched together into a composite map of cropland without requirements for overlap in the content of each individual image. Reduction in required image overlap allows composite aerial images of cropland to be constructed with far less flight time and research expenditure. The development and basic functionality of the device is discussed here. Deeper analysis of performance and applications of this technology is reserved for future publications.
Keywords: Entomology; Agricultural Automation; Aerial Imaging